Study of Women's Roles in Poverty Reduction - Fadillah Hanum (Universitas Negeri Semarang, 2025)
This research aims to analyze the influence of the gender development index, female labor force participation rate, and female per capita expenditure on poverty in 119 districts/cities in Java Island in the period 2020-2023. The research method uses a quantitative approach with panel data regression, utilizing secondary data from the Central Statistics Agency to explain the relationship between variables. The results of the study show that the gender development index, female labor force participation rate, and female per capita expenditure have a negative and significant effect on poverty. Increasing gender equality, women's participation in the labor market, and people's purchasing power have been shown to contribute to more effective poverty alleviation. This study emphasizes the importance of inclusive and gender-equitable development policies to optimally reduce poverty rates in various regions.